Effect of Participation in School Sports Teams on Middle School Students' Engagement in School - Mehmet Yanık (MDPI AG, 2018)
The aim of this study is to determine the effect of participation in school sports teams of students studying in middle school on their levels of school engagement. The relational screening model was used in the study. The study group of the research consisted of a total of 610 students selected by the random sampling method and studying at middle school level (fifth, sixth, seventh, and eighth grades). For analysis of the data obtained from the participants by means of the ‘School Engagement Scale’, descriptive statistics were calculated and interpreted with independent samples t-test and one-way analysis of variance (ANOVA). Based on the research findings, the mean level of school engagement of the participants was found to be 3.62 ± 0.51. In terms of the gender variable, a significant difference in favour of female participants was found. With respect to another variable, that of state of participation in school teams, it was determined that as length of participation in school teams increased, mean level of school engagement of the participants also increased. In conclusion, it was determined that participation in school teams made a positive contribution to students’ engagement in school, and it is recommended that in order to further increase students’ level of school engagement, measures should be taken to ensure students’ participation in school teams.